The manosphere and men’s health: unpacking the links between online communities, body dysmorphia and erectile dysfunction - Nick Ara Kamkari (Journal of Men's Health)
The increasing prevalence of erectile dysfunction (ED) among young men highlights a multifactorial issue rooted in the interplay of mental health challenges, societal pressures on male body image and risky health behaviors. Anxiety, depression and body dysmorphic disorder (BDD), particularly muscle dysmorphia, have surged in recent years, exacerbated by online communities within the “manosphere” that glorify hypermasculinity and physical perfection. These forums frequently promote the use of anabolic steroids and finasteride, substances that carry significant health risks, including hypogonadism, endocrine disruptions and sexual dysfunction. Anabolic steroid use, while yielding short-term muscular gains, has long-term consequences such as impaired fertility, mental health decline and ED. Similarly, finasteride commonly prescribed for androgenic alopecia, has been associated with libido reduction and mood disturbances. Online platforms often downplay these risks, encouraging young men to adopt these substances without full awareness of their potential adverse effects. The confluence of these physical and psychological factors creates a vicious cycle of appearance-related anxiety and ED, further compounding mental health issues. This article emphasizes the need for urologists to integrate mental health awareness and screening for risky behaviors into clinical practice. Tools such as the Patient Health Questionnaire-9 (PHQ-9) and direct inquiry about anabolic steroid and finasteride use can aid in identifying at-risk patients. Collaborative, multidisciplinary care involving mental health professionals, endocrinologists and dermatologists is crucial for effective management. Public health initiatives to raise awareness about these issues and promote healthy standards of masculinity are also essential. By addressing the root causes of body image dissatisfaction and fostering open dialogue, clinicians and communities can play a vital role in mitigating the growing burden of ED among young men and improving their overall health and well-being.